2020
DOI: 10.1111/cup.13877
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B‐cell lymphoma diagnosed by incisional random skin biopsy after failure of diagnosis using punch biopsy: A case report

Abstract: early-stage MF does not necessarily imply disease progression, but merely represents an activated T-cell phenotype. Lack of cytotoxic markers would support a memory T-cell origin as well. Further investigations about the pathomechanism of these phenomena are needed. The patient in this manuscript has given written informed consent to publication of his case details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Wu et al reported that high levels (>50%) of CD30 expression were observed in the intraepidermal tumor cells in 2% (4 of 202) patients with patch/plaque-stage MF. 5 Interestingly, the morphological, histopathological, and clinical features of CD30-positive MF were similar to those observed in patients with classic MF. A recent literature review describing patients with CD4/CD8 double-negative early MF reported CD30 immunopositivity (25%-50% expression) in 18.5% (5 of 27) patients.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Wu et al reported that high levels (>50%) of CD30 expression were observed in the intraepidermal tumor cells in 2% (4 of 202) patients with patch/plaque-stage MF. 5 Interestingly, the morphological, histopathological, and clinical features of CD30-positive MF were similar to those observed in patients with classic MF. A recent literature review describing patients with CD4/CD8 double-negative early MF reported CD30 immunopositivity (25%-50% expression) in 18.5% (5 of 27) patients.…”
supporting
confidence: 63%
“…However, there is no consensus on which of these two methods is more effective for diagnosis. 4,5 Thus, different institutions currently perform different RSB methods. Herein, we report a case where the punch method was insufficient for diagnosing IVLBCL, but the incisional method in the same patient was sufficient.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we diagnosed a case of intravascular large B-cell lymphoma using incisional biopsy after a false negative using punch biopsy. 4 The biopsy's sensitivity differed greatly between the report by Rozenbaum et al 1 and our previous data (50.0% vs 77.8%, respectively). 5 This might be attributable to their use of the punch method.…”
contrasting
confidence: 59%
“…8 When the diagnosis is suspected, various areas may be targeted for a biopsy including the brain, lung, bone marrow and skin, with or without signs of cutaneous disease. 2,4,5,9,10 Over the last 20 years, there have been studies 3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] noting the utility of random skin biopsy (RSB) in the diagnosis of IVBCL with many of these touting the relatively minimally invasive nature of RSB. As a result of the sensitivity (77.8%), specificity (98.7%) and positive and negative predictive values (96.6% and 90.6%, respectively) put forth by Matsue et al 3 and the ease of cutaneous biopsy, dermatologists have become part of the care team responsible for the diagnosis of IVBCL.…”
Section: Introductionmentioning
confidence: 99%